2013
DOI: 10.1016/j.exer.2013.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Zinc modulation of calcium activity at the photoreceptor terminal: A calcium imaging study

Abstract: There is abundant experimental evidence that zinc ions (Zn2+) are present in the synaptic vesicles of vertebrate photoreceptors, and that they are co-released with glutamate. Here we show that increasing the concentration of extracellular zinc (2 μM to 2 mM) suppresses the entry of calcium into the synaptic terminals of isolated salamander double cones. The resultant dose-dependent curve was fit by an inverse Hill equation having an IC50 of 38 μM, and Hill coefficient of 1.1. Because there is currently no reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…This notion was based on results by Wu and co-workers (Wu et al 1993), showing decreased calcium entry into photoreceptor terminals when exogenous zinc was applied to the salamander retina preparation. We have since confirmed these results, and in addition have shown that using chelators to remove endogenous zinc leads to a marked increase in both calcium entry (Anastassov et al 2013) and in the photoreceptor's dark current (Chappell et al 2008). These findings indicate that a reduced zinc concentration results in a concomitant increase in the discharge of glutamate, and led us to suggest that if endogenous zinc can suppress transmitter release, it may serve to protect the retina from the toxic effects of glutamate.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…This notion was based on results by Wu and co-workers (Wu et al 1993), showing decreased calcium entry into photoreceptor terminals when exogenous zinc was applied to the salamander retina preparation. We have since confirmed these results, and in addition have shown that using chelators to remove endogenous zinc leads to a marked increase in both calcium entry (Anastassov et al 2013) and in the photoreceptor's dark current (Chappell et al 2008). These findings indicate that a reduced zinc concentration results in a concomitant increase in the discharge of glutamate, and led us to suggest that if endogenous zinc can suppress transmitter release, it may serve to protect the retina from the toxic effects of glutamate.…”
supporting
confidence: 56%
“…We have since confirmed these results, and in addition have shown that using chelators to remove endogenous zinc leads to a marked increase in both calcium entry (Anastassov et al . ) and in the photoreceptor's dark current (Chappell et al . ).…”
mentioning
confidence: 99%
“…Depolarization of the retinal neurons can induce zinc release at the plexiform layers, which provided the first evidence for the hypothesized neuro modulator role for zinc in the retina . Endogenous zinc is co‐released with glutamate from synaptic terminals of photoreceptors and, by negative feedback, reduces calcium entry and concomitant vesicular release of glutamate . This is, therefore, likely to protect the retina from glutamate excitotoxicity …”
Section: Zinc In the Normal Retinamentioning
confidence: 99%
“…[68,131,132] Endogenous zinc is co-released with glutamate from synaptic terminals of photoreceptors and, by negative feedback, reduces calcium entry and concomitant vesicular release of glutamate. [81,83] This is, therefore, likely to protect the retina from glutamate excitotoxicity. [83] Zinc can be released from the cellular compartments or stores by molecules such as MTs, by external stimuli.…”
Section: Zinc In the Normal Retinamentioning
confidence: 99%
See 1 more Smart Citation